One Day at the Sands: Exploring Las Vegas' Intangible Heritage through Virtual Reality. Issue 1 (March 2015) - Martina, Andrea; Bottino, Andrea; Rubino, Irene; Cook, Daniel
The construction, negotiation and dissemination of cultural heritage in the digital era can take advantage of several approaches, including Virtual Reality (VR). Leveraging on the provision of contextualized multimedia content, VR can foster awareness about the histories of specific times and places, encouraging personal interpretative processes. This paper presents the design, implementation and evaluation of "One Day at the Sands", a VR application aimed at conveying the atmosphere of one of the most famous casinos in Las Vegas from the 1950s onwards. First, we collected a digital database, including a wide range of historical material; then, we developed a presentation medium that allows viewers to navigate the virtual reconstructions and access the archival material following their curiosity and interests. User tests underlined the capability of the application to facilitate a deep and meaningful exploration of the contents reinforcing the argument that virtual reality solutions represent valuable tools to engender awareness and explorative attitudes towards heritage.